Food Management in Pesantren based on Integrated Farm Education and Entrepreneurship - Umam, Khoirul; Janan, Mumtaz Jinanul; Roslan, Isma Aulia (The Institute of Research and Service Community IPMAFA Pati, 2023)
Food is one of many global challenges that require significant attention. Indonesia, with the majority Muslim population and the largest number of pesantren in the world, has become the second biggest food contributor in the world. It is inconsistent with the principles of Islam. This research is concerned with the implementation of an integrative approach to food management in pesantren through the integration of agriculture and entrepreneurship education. Pesantren, as a self-sustaining community, provides an ideal medium to explore sustainable practices. This research is a qualitative case using the triangulation method with both observation and documentation techniques. This research involves the implementation of a structured education program within the Pesantren that combines agricultural practices and entrepreneurial skills. The results highlighted that by integrating agriculture and entrepreneurship education, pesantren communities significantly contributed to reducing the number of food. The results of this research demonstrate the effectiveness of integrating agriculture and entrepreneurship education in reduction, honing skills, and fostering a sense of responsibility and sustainable practices among residents. The findings emphasize the importance of integrating education and entrepreneurship for holistic food management in Pesantren. The discussion delved into the social, economic, and environmental implications, highlighting the potential for scalability and adaptation in other similar settings. This integrative approach does more than solve the food problem; instead, it also contributes to developing people skills and sustaining the community in Pesantren.